Efforts to Improve the Learning Outcomes of Junior High School Students Through the Medium of Learning Video - Zulfa Candraningrum; Agus Efendi; Endar Suprih Wihidayat (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
This classroom action research aims to improve student learning outcomes in the Indonesian language through the use of learning videos. The research was conducted in two cycles, with each cycle consisting of four stages: planning, action implementation, observation, and reflection. During the observation stage, researchers collected data by observing the activities of teachers and students as they used the video learning media. The results showed a significant improvement in learning outcomes. The percentage of students meeting the learning completion criteria increased from an initial 31.25% to 46.9% in the first cycle, and further rose to 84.38% in the second cycle. Additionally, students demonstrated higher participation and were more active during learning activities.